The case for intra-operative X-ray in cochlear implantation: Four illustrative cases and literature review. (2nd November 2022) - Yu, Cheryl; Debs, Sarah; Singh, Rhea; Kastetter, Sean; Pierre-Louis, Akilah; Coelho, Daniel H.
Abstract : Objectives: To demonstrate the utility of routine intraoperative plain film imaging in optimizing outcomes in cochlear implantation. Introduction: Evolving surgical techniques, programming, and electrode arrays have all improved performance outcomes in cochlear implantation. Yet despite decreasing complication rates, electrode misplacement remains a common occurrence. Utilization of intraoperative confirmational tools (radiologic, electrophysiologic) remains unstandardized despite the acknowledged importance of proper electrode positioning. The purpose of this article is to illustrate the use and benefits of intraoperative X-ray (IOXR) in four cases, particularly in cases of normal electrophysiologic testing. Methods: Four cases performed by an experienced CI surgeon are discussed where electrode malposition was only detected through X-ray. Literature review was performed on the use of intraoperative imaging, focusing on plain film radiography. Results: Case 1–3 describe examples of resistance-free electrode insertion in patients with normal pre-operative imaging. Intraoperative impedances and neural response telemetry (NRT) were normal. However, IOXR ultimately revealed tip fold-over prompting array repositioning. Case 4 describes an elective replacement of a soft-failing device. Resistance was encountered during array insertion, with IOXR demonstrating incomplete insertion compared with prior imaging. Positioning was revised to achieve pre-revision insertion depth, demonstrating the utility of prior IOXR in revision cases. Literature review of IOXR is discussed. Conclusion: Appropriate placement of the electrode is paramount to successful CI outcomes. These cases illustrate IOXR as a safe, effective method to ensure optimal placement even in cases of normal electrophysiologic testing, supporting its routine use even by the most seasoned surgeons.